Comparative Study of Maize Agronomics Performance under low Nitrogen Soil Availability, in Southern Savanna of DR Congo - Tshiabukole, Jean Pierre Kabongo; Khonde, Gertrude Pongi; Kankolongo, Amand Mbuya; Jadika, Carcy Tshimbombo; Vumilia, Roger Kizungu (Afrika Focus, 2019)
To determine the growing and yield performance of low nitrogen tolerant maize varieties under fertilized and unfertilized conditions, a study was conducted at the Mvuazi Research Center. Nine varieties were tested with and without fertilizer using the micro-dosing method, following the randomized complete block design with two factors. The results showed a difference among varieties in both crop conditions. The average yield with fertilizer was higher than the yield without fertilizer. The varieties LNTP-W C4 and LNTP-Y C7 registered 5.9 t/ha and 3.6 t/ha respectively under fertilized crop conditions and 7.14t/ha and 7.12t/ha under unfertilized crop conditions. Thus, using Low-N can minimize production costs by improving the productivity of soils low in Nitrogen typical of conditions of the southwestern savanna. KEY WORDS: LOW NITROGEN SOIL, LNTP, MAIZE PRODUCTION, FERTILIZER, SAVANNA, INERA-DRC